Research Ready Program: A First in Regional South Australia - Penman, Joy; Oliver, Mary (Australian and International Journal of Rural Education, 2012)
In response to the South Australian Certificate of Education (SACE) Board's introduction in 2010 of the new Research Project subject, the University of South Australia's Centre for Participation and Community Engagement took the opportunity to engage further with school students by organising the Research Ready Program. The adoption of the program for local Year 11 government high school students by the University's Centre for Regional Engagement at Whyalla is the focus of this paper. The program, consisting of seven sessions spread across two school terms aimed to assist students identify a research topic and develop their research project, learn about the research process, support professional development of school staff and enhance school students' aspirations and pathways to university. The paper explores the learning that transpired in order to meet the educational needs of high school students embarking on this new subject and discusses the reflections of participating university academic staff and school teachers. Questionnaire responses by participating students showed that they rated the program as 'good' to 'excellent' and believed that it would help them to complete their research projects successfully. The impact of the program on students' aspirations to pursue university studies, and the implications for a regional university campus and its community, are also examined.